Assessing Labor Market Conditions in Canada with Public-Use Microdata - Etienne Lalé (Institute of Labor Economics (IZA), 2024)
We extend Nakamura et al. (2019, 2020)'s approach of using the publicly available microdata files of the Labour Force Survey (LFS) to construct worker transition rates across employment, unemployment, and inactivity. Our approach involves estimating and applying a scaling factor that has been proposed in earlier research as a way of capturing the relative intensity of job search from inactivity compared to unemployment. This factor provides enough structure to prevent arbitrary splitting of unemployment outflows between employment and inactivity. In turn, the estimated job search factor can be used in a few simple step-by-step instructions applied to the LFS public files to assess near real-time labor market conditions in Canada. An analysis of the recent dynamics of worker flows illustrating the practicality of our approach highlights that transition rates: (a) from employment to unemployment have fallen over time (b) from unemployment to employment were unusually high during the pandemic and (c) have regional differences.
Keywords: E24; J21; J63; 330; employment; unemployment; labor force participation; gross worker flows